2000
DOI: 10.1002/(sici)1096-9888(200002)35:2<189::aid-jms929>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Double transacetalization of diacylium ions

Abstract: A novel gas‐phase reaction of diacylium ions of the OCX+CO type (X = N, CH) is reported: double transacetalization with cyclic acetals or ketals. The reaction is exothermic and highly efficient, and forms members of a new class of highly charged‐delocalized ions: cyclic ionic diketals. Pentaquadrupole double‐ and triple‐stage mass spectrometric (MS2 and MS3) experiments reveal the high double transacetalization reactivity of OCN+CO and OCCH+CO, whereas the synthesis of differently substituted cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Any reactant ion with a Lewis acid site able to participate in electrophilic addition and a Lewis basic site able to effect nucleophilic ring-closure is in principle eligible to undergo the Eberlin reaction. Indeed, the reaction has been observed not only for acylium ions (R−C + O) but also for many other amphoteric ions such as thioacylium (R−C + S), , carboxonium (H 2 CO + −R), carbosulfonium (H 2 CS + −R), distonic or distonoid radical acylium ( • R−C + O, R = alkyl, allyl, or phenyl), , diacylium (OCN + CO), , sulfinyl (R−S + O), , arylsulfenium (ArS + ), borinium ((RO) 2 B + ), silylium ((RO) 3 Si + ), phosphonium (R 2 P + O), , arylnitrenium (ArNH + ), nitronium (NO 2 + ) 153 and hetarynium ions (2-pyridyl, 2-pyrrolyl cations, and their analogues) …”
Section: Scope Of the Eberlin Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any reactant ion with a Lewis acid site able to participate in electrophilic addition and a Lewis basic site able to effect nucleophilic ring-closure is in principle eligible to undergo the Eberlin reaction. Indeed, the reaction has been observed not only for acylium ions (R−C + O) but also for many other amphoteric ions such as thioacylium (R−C + S), , carboxonium (H 2 CO + −R), carbosulfonium (H 2 CS + −R), distonic or distonoid radical acylium ( • R−C + O, R = alkyl, allyl, or phenyl), , diacylium (OCN + CO), , sulfinyl (R−S + O), , arylsulfenium (ArS + ), borinium ((RO) 2 B + ), silylium ((RO) 3 Si + ), phosphonium (R 2 P + O), , arylnitrenium (ArNH + ), nitronium (NO 2 + ) 153 and hetarynium ions (2-pyridyl, 2-pyrrolyl cations, and their analogues) …”
Section: Scope Of the Eberlin Reactionmentioning
confidence: 99%
“…They can be prepared by the reaction of simple diones with vicinal diols in acidic solution . In the gas phase, an interesting double polar transacetalization of sing ly c harged diacylium ions of the OCX + CO type (X = N, CH) with cyclic acetals has been reported. , The reaction is exothermic and highly efficient and forms a new type of highly charge-delocalized ion, an ionic diacetal (Scheme d). In the case of the reaction of OCN + CO with 2-methyl-1,3-dioxolane, ab initio calculations show that mono-transacetalization is exothermic by 33.3 kcal/mol, while the double transacetalization is 43.1 kcal/mol exothermic .…”
Section: 1 Carboxonium Ions and Related Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion-molecule transacetalization reactions of heterocumulenes of the type [ONCNXNCNO] + (X = N and CH) have been studied using multistage mass spectrometry experiments. 182 Stepwise double transacetalization with cyclic acetals or ketals is observed and results in very stable charge-delocalized ions as shown in eqn. (42).…”
Section: Reactions Of Organic Ions Containing Heteroatomsmentioning
confidence: 99%
“…used an FT-ICR and an ion trap mass spectrometer to study the ion^molecule reactions observed in the ionization of organophosphorus esters (trimethyl phosphite, triethyl phosphite, dimethyl phosphonate, trimethyl phosphate and 2,2-dichlorovinyl dimethyl phosphate). The phosphonates and phosphates mainly give proton-bound dimers and the phosphites give condensation products of the general formula [(RO) 3 P (RO) 2 P] .Eberlin and co-workers91 have used pentaquadrupole (QqQqQ) mass spectrometry to explore the reactions of SF n (n 1^5) ions with benzene, acetonitrile, and pyridine. With benzene, SF reacts by an electrophilic substitution pathway to give benzenesulfenyl £uoride, C 6 H 5 ^SF .…”
mentioning
confidence: 99%